Rickettsia as an agent of neglected Rickettsia infection - Tjampakasari, Conny Riana; Kiranasari, Ariyani; Abas, Ghina Mutiara (Journal of Clinical Microbiology and Infectious Diseases, 2024)
Rickettsia is an obligate parasite of certain arthropods (especially ticks, mites, and ticks) and can cause serious diseases. OmpA dan OmpB is a surface protein that facilitates Rickettsia’s fast attachment and entry into the endothelium. Clinical symptoms are usually characterized by self-limited acute fever in both humans and other animals. Diseases caused by Rickettsia are endemic in almost all around the world, including Indonesia. Rickettsia diseases include epidemic typhus, murine typhus, scrub typhus, and spotted fever. Culture, nucleic acid amplification, and serological tests can be used as diagnostic examinations. The serological test is the gold standard of Rickettsial diagnostic, even though molecular tests have been developed. Diagnostic limitations mean that rickettsiosis is often overlooked as a cause of infection. Rickettsia eradication was carried out by giving tetracycline, chloramphenicol, and rifampin. Vaccines are not yet available so prevention and appropriate use of antibiotics based on the diagnostic examination will determine the success of eradication.